2019
DOI: 10.1039/c9fo00654k
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium tyrobutyricum alleviates Staphylococcus aureus-induced endometritis in mice by inhibiting endometrial barrier disruption and inflammatory response

Abstract: Endometritis is an inflammatory disease of the uterus caused by bacterial infection, and it affects both human and animal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…[24][25][26] Ct, a Gram-positive bacterium, has been shown to prevent LPS-induced intestinal barrier dysfunction in vitro and alleviate Staphylococcus aureus-induced endometrial inflammation in vivo. [27,28] However, whether Ct could alleviate intestinal inflammation is still unclear. In this study, we found that 10 7 CFU mL −1 Ct could alleviate inflammation in the duodenum and 10 8 CFU mL −1 Ct protected against duodenal and ileal inflammation, indicating that Ct was a potential prophylactic probiotic in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Ct, a Gram-positive bacterium, has been shown to prevent LPS-induced intestinal barrier dysfunction in vitro and alleviate Staphylococcus aureus-induced endometrial inflammation in vivo. [27,28] However, whether Ct could alleviate intestinal inflammation is still unclear. In this study, we found that 10 7 CFU mL −1 Ct could alleviate inflammation in the duodenum and 10 8 CFU mL −1 Ct protected against duodenal and ileal inflammation, indicating that Ct was a potential prophylactic probiotic in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…When inflammation occurs, the IκB kinase triggers IκB-α ubiquitination and proteasome degradation via phosphorylation, which allows NF-κB p65 to accumulate in the nucleus to elicit the production of cytokines, such as TNF-α, IL-1β, and IL-6 ( 42 ). Previous studies have shown that S. aureus infection can increase the phosphorylation of IκB-α and p65 proteins, and activate NF-κB signaling pathway in lung and uterine tissues ( 43 , 44 ). In this study, the phosphorylation of IκB-α and p65 proteins in mammary tissues were increased significantly after S. aureus infection, which indicated that NF-κB was involved in the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that Clostridium tyrobutyricum could be used to produce higher butyric acid via bacterial fermentation (5)(6)(7). Recently, C. tyrobutyricum has been revealed to protect barrier function in different tissues, including the gut (8), testis (9), and endometrium (10). A new study about the genomic analysis of C. tyrobutyricum pointed out that C. tyrobutyricum is a potential bacteria in regulating health in human beings (11).…”
Section: Introductionmentioning
confidence: 99%